Design and fabrication of flying saucer utilizing coanda effect - Aabid, Abdul; Khan, Sher Afghan (Institute of Physics Publishing, 2018)
Coanda effect is used in several engineering applications with distinctive designs and structures. It is also applied in aircrafts flying at low speeds for a comfortable ride. In this paper, we have designed and modelled Coanda effect in terms of a flying saucer. The fabrication was done by means of structural and electronic components. Electrical motor was used as a propeller to take off and land vertically (VTOL) along with hovering capability. The rotor disc diameter is smaller than the bulbous body unlike a helicopter which makes to fly very stable. Control flaps were used to regulate the path by altering the flow over the streamlined body. The model was then tested with a remote control. Numerical Simulation of the tesla turbine was done using ANSYS 14.5 software and displacements were obtained by applying different forces on designed model. CATIA V5 was used to analyse the shaft of the model to get minimum value of torque at which the shaft starts to deform. © Published under licence by IOP Publishing Ltd.